Fluorescence-Guided Surgery: A Review on Timing and Use in Brain Tumor Surgery - Schupper, Alexander J.; Rao, Manasa; Mohammadi, Nicki; Baron, Rebecca; Lee, John Y. K.; Acerbi, Francesco; Hadjipanayis, Constantinos G. (Frontiers in Neurology, 2021)
Fluorescence-guided surgery (FGS) allows surgeons to have improved visualization of tumor tissue in the operating room, enabling maximal safe resection of malignant brain tumors. Over the past two decades, multiple fluorescent agents have been studied for FGS, including 5-aminolevulinic acid (5-ALA), fluorescein sodium and indocyanine green (ICG). Both nontargeted and targeted fluorescent agents are currently being used in clinical practice, as well as under investigation, for glioma visualization and resection. While the efficacy of intraoperative fluorescence in studied fluorophores has been well established in the literature, the effect of timing on fluorophore administration in glioma surgery has not been as well depicted. In the past year, recent studies of 5-ALA use have shown that intraoperative fluorescence may persist beyond the previously studied window used in prior multicenter trials. In the following review, the authors will describe the temporal nature of the various fluorophores used in glioma surgery, and what remains uncertain in FGS.